Application of operational-based strategic intervention model for evaluating office buildings energy efficiency performance - SENNAROĞLU, BAHAR (SPRINGER, 2021)
The operational management and strategic interventions for energy efficiency (EE) of facilities could be optimised if interventions and decision-making processes are well integrated. Hence, this study developed a conceptual dual model for building energy performance (BEP) as a composite model based on prior theories. The theoretical study variables were interventions (technical and operational) and decision-making (management) factors (manifest variables) derived from an extensive literature review. Likewise, the constructs (latent variables) were the aggregated data of the intervention/decision-making evident factors used in the composite scale model. These constructs define the identifiable EE (management) manifest factors and classify them for standardised EE management practices. This paper describes the effects and the causal relationship between constructs derived from these factors that impact BEP via the composite scale model. An online self-administered questionnaire was used in gathering information from the occupants of selected office buildings in two countries (Nigeria and the UK). Structural equation modelling was engaged in evaluating the structure of the composite scale model that serves as a merger of isolated critical factors that affect BEP improvement. The model has four parts: the strategic driver, management policy, operational and building energy performance constructs as distinct sub-models. The results of the model evaluation reveal that the collected data fit the hypothesised dual model and have good fits. The models are not significantly different; they help investigate the fundamental relationship between the constructs. The result also reveals a strong positive correlation of management policy with strategic drivers for EE; strategic drivers with the use of building energy performance model; and management policy with operational EE practices. Path evaluation shown on the dual model specified the hypothesised causal relationship amongst constructs and strategic driver as the only significant positive mediator. Furthermore, the study integrates interventions and decision-making in a new dual model for improving BEP for diagnostic and solution purposes. Facility managers and owners could use the dual model as a strategic and tactical decision-making implement in managing low-carbon office BEP.
Keywords: Dual model approach; Strategic drivers; Energy efficiency; Office building performance; Operational facilities management; Structural equation modelling